(TRANS)formando no Ensino Superior: Trajetórias de estudantes Travestis e Transexuais na Universidade Federal de Uberlândia - Silva, Rosilaine Cristina (2022)
The project is associated with the "Saberes e Práticas Educativas" research from Programa de Pós-graduação em Educação da Universidade Federal de Uberlândia (PPGED/UFU), as well as Grupo de Pesquisa Educação, Sexualidades e Performatividades (GPESP). It aimed understand how the access, stay and experience process was made for transvestites and transexuals students, who are enrolled in graduation and undergraduation from UFU. It followed the theoretical benchmark in critical studies and poststructuralist about gender and sexuality. The method of research was an exploratory surgery and also qualitative approach. The instruments applied to data measurement was: a online survey form and an interview following a script prepared by the research author, each one conducted remotely, because of COVID-19 pandemic. During the research, it noticed that thematic is rising through the academy, it showed up an agreement between researchers in production of new knowledge based on analyse the singularity and diversity in the society. We conclude that students, in majority, enrolled at UFU by ENEM/SISU and each student made their own strategy to keep their existence and stay into University. Join university helped them find out more about themselves, socialize with their pairs, in groups, social movements or with CRAIST. When asked about staying, they reported some difficulties, as finances, which showed the necessity to work and study. Another report was about using their social name at UFU, they told that it's a hard bureaucratic process. The transphobia experienced by them was from each form, fiscally, mentally, symbolic. And, in much cases, they did not get any right treatment, which make them do not believe on report it. The affirmative policies approached by UFU had been cited and help to understand it over resolutions and administrative rules, it's important to talk to create ways and develop actions that improve the reality of them in UFU. According to the research, we believe that the Sexual Diversity and Gender Commission of UFU will have a great responsibility, once it'll be able to find what needs to be improved by superior management of UFU and support promotion of constitutional rights of trans students.